The Genesis of Web Series As A Popular Form of Digital Entertainment: An Exploratory Analysis of Creative & Business Potential in Indian Context - Manju Rughwani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Technology disruption in the Indian Media and Entertainment space has changed the way we consume content across all platforms. Lately, India has witnessed the increased number of OTT (Over the Top) Content players as well as start-ups targeted towards online video. The entry of Amazon Prime Video and Netflix in Indian shores has propelled the demand for niche online content viewing. The research paper will explore the fantasy for web series among the New-Age audiences. It will explore the treatment of story-telling concepts in terms of storylines, programming, production techniques in comparison with television series formats. The second part of the paper will attempt to identify the reasons for business potential for web series formats. The paper will draw to the conclusion that web series is the future of digital entertainment and has huge business potential. It concluded that with the rise of digital millennials and subscribers and accessibility to smartphones, web seriescan have a large geographical reach.